2017
DOI: 10.3389/fimmu.2017.01351
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Plasmacytoid Dendritic Cells in Regulating Gene Expression and Innate Immune Responses to Human Rhinovirus-16

Abstract: Though human rhinoviruses (HRVs) are usually innocuous viruses, they can trigger serious consequences in certain individuals, especially in the setting of impaired interferon (IFN) synthesis. Plasmacytoid dendritic cells (pDCs) are key IFN producing cells, though we know little about the role of pDC in HRV-induced immune responses. Herein, we used gene expression microarrays to examine HRV-activated peripheral blood mononuclear cells (PBMCs) from healthy people, in combination with pDC depletion, to assess whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Antigen-presenting dendritic cells are essential for detecting invading pathogens and activating other immune cells; therefore, they play a role in both innate and adaptive immune response. Previous work from our research group confirmed pDC as the primary and vital IFNα producer cell type (Xi et al 2015;Xi et al 2017), and as expected, we saw that the pDC marker CLEC4C was more highly expressed in the IFN-high group at baseline than in the IFN-low group, both in whole blood and PBMC (Whole blood, Table 4:1; PBMC, Figure 4:5). CLEC4C remained as a significant differentially expressed gene in the transcriptome analysis, indicating that pDC numbers at baseline are a key factor predicting the magnitude of the IFNα response to viral stimulation.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Antigen-presenting dendritic cells are essential for detecting invading pathogens and activating other immune cells; therefore, they play a role in both innate and adaptive immune response. Previous work from our research group confirmed pDC as the primary and vital IFNα producer cell type (Xi et al 2015;Xi et al 2017), and as expected, we saw that the pDC marker CLEC4C was more highly expressed in the IFN-high group at baseline than in the IFN-low group, both in whole blood and PBMC (Whole blood, Table 4:1; PBMC, Figure 4:5). CLEC4C remained as a significant differentially expressed gene in the transcriptome analysis, indicating that pDC numbers at baseline are a key factor predicting the magnitude of the IFNα response to viral stimulation.…”
Section: Discussionsupporting
confidence: 88%
“…LILRA4 was previously identified as being stably expressed in unstimulated pDC compared to other immune cell types (Cho et al 2008). CLEC4C was recognised as a pDC specific cell marker in 2001 (Dzionek et al 2001), and we previously showed that it is markedly reduced in pDC depleted cell populations (Xi et al 2017), therefore we used those two markers to detect pDC population ( Figure 2:1:A). We compared whole blood to PBMC, and as expected the pDC frequency was higher in PBMC than in whole blood ( Figure 2:1:B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations